Surface Plasmon Resonance Immunoassay for Biotin Determination on a Home-made Instrument. (2017) - Chen, Xing; Zhang, Lulu; Cui, Dafu
Abstract: In this paper, a home-made SPR analytical system and a denaturalized bovine serum albumin (dBSA) SPR chip were used to detect biotin based on the method of an inhibition immunoassay. The experimental was compared with a commercial protocol. The conditions of regeneration were optimized. The dBSA SPR chip was fabricated by a self-assembling method and the derivative of biotin was immobilized on the dBSA SPR chip by using a on-line mode. A commercial instrument and a dextran-SPR-chip (CM5) were used to implement the same experiments. Based on the experiments of immune reactions between biotin antibody and biotin derivative, the biotin antibody concentration was optimized at about 5 μg/mL in order to obtain highly sensitivity, which was used in the followed inhibition immunoassays. The lowest detection limit for biotin is 0.1 μg/mL with a detection range of 0.1-1000 μg/ml by using our home-made instrument and the dBSA-SPR-chip. The detection results of our instrument and dBSA SPR chip are comparable with the commercial protocol. Our home-made instrument and dBSA-SPR-chips can be also applied to detect other small molecules based on the indirect inhibition immunoassay.